Fractional Exponents: Rules for Multiplying & Dividing

••• jacoblund/iStock/GettyImages

Learning to deal with exponents forms an integral part of any math education, but thankfully the rules for multiplying and dividing them match the rules for non-fractional exponents. The first step to understanding how to deal with fractional exponents is getting a rundown of what exactly they are, and then you can look at the ways you can combine exponents when they’re multiplied or divided and they have the same base. In brief, you add the exponents together when multiplying and subtract one from the other when dividing, provided they have the same base.

TL;DR (Too Long; Didn't Read)

Multiply terms with exponents using the general rule:

xa + xb = x(a + b)

And divide terms with exponents using the rule:

xa ÷ xb = x(ab)

These rules work with any expression in place of a and b, even fractions.

What Are Fractional Exponents?

Fractional exponents provide a compact and useful way of expressing square, cube and higher roots. The denominator on the exponent tells you what root of the “base” number the term represents. In a term like xa, you call x the base and a the exponent. So a fractional exponent tells you:

x1/2 = √x

The denominator of two on the exponent tells you that you’re taking the square root of x in this expression. The same basic rule applies to higher roots:

x1/3 = ∛x

And

x1/4 = 4√x

This pattern continues. For a concrete example:

91/2 = √9 = 3

And

81/3 = ∛8 = 2

Fraction Exponent Rules: Multiplying Fractional Exponents With the Same Base

Multiply terms with fractional exponents (provided they have the same base) by adding together the exponents. For example:

x1/3 × x1/3 × x1/3 = x (1/3 + 1/3 + 1/3)

= x1 = x

Since x1/3 means “the cube root of x,” it makes perfect sense that this multiplied by itself twice gives the result x. You may also run into examples like x1/3 × x1/3, but you deal with these in exactly the same way:

x1/3 × x1/3 = x (1/3 + 1/3)

= x2/3

The fact that the expression at the end is still a fractional exponent doesn’t make a difference to the process. This can be simplified if you note that x2/3 = (x1/3)2 = ∛x2. With an expression like this, it doesn’t matter whether you take the root or the power first. This example illustrates how to calculate these:

81/3 + 81/3 = 82/3

= ∛82

Since the cube root of 8 is easy to work out, tackle this as follows:

∛82 = 22 = 4

So this means:

81/3 + 81/3 = 4

You may also encounter products of fractional exponents with different numbers in the denominators of the fractions, and you can add these exponents in the same way you’d add other fractions. For example:

x1/4 × x1/2 = x(1/4 + 1/2)

= x(1/4 + 2/4)

= x3/4

These are all specific expressions of the general rule for multiplying two expressions with exponents:

xa + xb = x(a + b)

Fraction Exponent Rules: Dividing Fractional Exponents With the Same Base

Tackle divisions of two numbers with fractional exponents by subtracting the exponent you’re dividing (the divisor) by the one you’re dividing (the dividend). For example:

x1/2 ÷ x1/2 = x(1/2 – 1/2)

= x0 = 1

This makes sense, because any number divided by itself equals one, and this agrees with the standard result that any number raised to a power of 0 equals one. The next example uses numbers as bases and different exponents:

161/2 ÷ 161/4 = 16(1/2 – 1/4)

= 16(2/4 – 1/4)

= 161/4

= 2

Which you can also see if you note that 161/2 = 4 and 161/4 = 2.

As with multiplication, you may also end up with fractional exponents that have a number other than one in the numerator, but you deal with these in the same way.

These simply express the general rule for dividing exponents:

xa ÷ xb = x(ab)

Multiplying and Dividing Fractional Exponents in Different Bases

If the bases on the terms are different, there is no easy way to multiply or divide exponents. In these cases, simply calculate the value of the individual terms and then perform the required operation. The only exception is if the exponent is the same, in which case you can multiply or divide them as follows:

x4 × y4 = (xy)4

x4 ÷ y4 = (x ÷ y)4

References

About the Author

Lee Johnson is a freelance writer and science enthusiast, with a passion for distilling complex concepts into simple, digestible language. He's written about science for several websites including eHow UK and WiseGeek, mainly covering physics and astronomy. He was also a science blogger for Elements Behavioral Health's blog network for five years. He studied physics at the Open University and graduated in 2018.

Dont Go!

We Have More Great Sciencing Articles!